Wisata Budaya: Identifikasi Potensi Wisata Budaya Berbasis Masyarakat Di Kota Bandung - Desmala Sari; Evi Novianti; Rifqi Asyari (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Cultural Tourism: Identification of Community-Based Cultural Tourism Potential In Bandung. As a city with many nicknames as City of Heritage, Bandung has cultural tourism assets such as monuments or historical buildings that can be a special attraction for everyone who visits. Experts needed to manage these tourism assets, one of the concepts of tourism asset management can be applied with the local community who are known as Community Based Tourism (CBT). This article tries to identify the potential of existing community-based heritage tourism attractions to support the development of Bandung City as a City of Cultural Tourism. The results of this study are many tourist attractions that can be developed into community-based cultural tourism, one of which is the Braga Square area, but there is still a need for better management such as packaging or tour packages and markets to visit existing tours.